How to Farm in the Midst of Climate Change? A Systematic Review of Farmer Adaptation Strategies in Countries with Extreme Climate Change - Putu Wijangga (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
Climate change is becoming a multidimensional threat to the global agricultural sector, demanding urgent adaptation especially in countries with extreme climates, which has a serious impact on farmers' productivity and livelihoods. This systematic review aimed to analyse how farmers are adapting their farming practices in the midst of extreme climate change, as well as to identify the most common and effective adaptation strategies, including the barriers faced. Using the PRISMA guidelines, the study screened 1,734 articles from the Scopus database, resulting in 52 final review articles that met the eligibility criteria. The results showed that farmers implemented various adaptation strategies grouped into five main themes: agronomy & crops, water resource management, social & economic adaptation, technology & information-based adaptation, and institutional & community-based adaptation. Agronomic and water management strategies are most widely applied. However, the implementation of adaptation is faced with significant obstacles, namely limited access and availability of resources, lack of knowledge, information, and support, as well as social, institutional, and behavioral constraints. Bibliometric visualizations confirm "climate change" and "smallholder farmers" as central focuses, with increasing interest in "climate-smart agriculture". In conclusion, smallholder adaptation is a multidimensional effort that requires integrated and holistic support from government policies as well as all stakeholders to build long-term resilience.